A study on the construction of honesty culture in colleges and universities from the perspective of "three complete education" - Nie , Longxue (American Journal of Education and Learning, 2023)
The report of the 20th National Congress of the Communist Party of China pointed out that we must adhere to the strategy of giving priority to education, accelerate the construction of a high-quality education system, develop quality education, and promote educational equity. The construction of integrity culture is an important measure of quality education in colleges and universities, and it undertakes the dual tasks of educating people and anti-corruption. This paper uses the survey method to carry out integrity culture education in colleges and universities under the perspective of "three complete education", and sorts out the "three complete education" and The relationship between the construction of integrity culture in colleges and universities provides better theoretical support for the smooth development of integrity culture education in colleges and universities, builds a long-term mechanism for integrity culture, promotes the effective implementation of the construction of integrity culture in colleges and universities, implements the fundamental task of cultivating people, and cultivates morality, intelligence, physical beauty Builders and successors of socialism with all-round development of labor, and accelerate the construction of a strong education and cultural power.